Capital Structure Theories in Finance Research: A Historical Review - Ferdous, Lutfa T (Australian Finance & Banking Review, 2019)
Capital structure in one of the most converse and vital issues in the finance literature. This theoretical review of capital structure provides a synthesis of the theory utilised in capital structure literature. This theoretical review explains two categories of theories that examine the optimum capital structure of a firm. Functional market theories, which propose firms conduct share transaction without being used transaction costs and ii) costly transaction theories. The first group consists of the original capital structure theories of Modigliani and Miller (1958, 1963), Miller (1977), and De Angelo and Masulis (1980). The second range of theories captures the various effects of costly capital market transactions: Pecking Order Theory" accredited to Donaldson (1961); the debt capacity theories that depend on bankruptcy to limit a firm's use of debt financing (Robicheck and Myers, 1966) the agency models developed by Jensen and Meckling (1976), Myers (1977), Smith and Warner (1979); and signalling model by Ross (1977). Recent capital structure literature explored into an analytical structure building up the major contributions starting with the development of agency and bankruptcy theory. These theories are connected with the outcome from financing choices to real debt-equity decisions. Finally, we finish our review with established studies that explore the significances of leverage- equity relationship, as well as its determinants.